Breaking Boundaries in Inclusive Education: A Narrative Review of Pedagogical, Technological, and Policy Practices and Challenges in Regular Schools - Malizal, Zelynda Zeinab; Rahman, Najib Aulia (Yayasan Sinergi Kawula Muda, 2024)
Inclusive education for children with special needs is a central principle in global education reform, aiming to ensure equitable access and participation in mainstream schooling. This narrative review explores current practices, challenges, and innovations in inclusive education, synthesizing insights from international literature. Using a structured search across databases such as Scopus, PubMed, Google Scholar, ERIC, and JSTOR, the review identifies key factors influencing inclusive learning: teacher training, educational technology, family engagement, curriculum flexibility, policy frameworks, and funding. Findings indicate that personalized learning technologies, when supported by trained educators, enhance student engagement and academic performance. Teachers who undergo inclusive pedagogical training demonstrate higher confidence and competence in addressing diverse learner needs. Family involvement and community support emerge as critical enablers of social and emotional development in inclusive settings. Moreover, flexible curricula and supportive policies correlate with improved student outcomes. However, persistent barriers remain, including lack of funding, infrastructural limitations, societal stigma, and inconsistent implementation of inclusive policies. This review emphasizes the need for comprehensive policy reforms, sustained investments in teacher development, adaptive curricula, and cross-sector collaboration. It also highlights the importance of equity-driven technology integration to address existing disparities. Future research should prioritize longitudinal and participatory studies that reflect the lived experiences of students with special needs. The study underscores that achieving truly inclusive education requires systemic transformation supported by cultural change, educational equity, and collaborative partnerships.